Neutronics and thermal-hydraulics coupling analysis for a small lead-based fast reactor based on the discrete ordinate nodal and parallel channel method - Fang, Chao; Peng, Xingjie; Zhao, Chen; Lou, Lei; Zhang, Bin; Wang, Lianjie; Chen, Zhang; Li, Qing (Frontiers in Energy Research, 2023)
The full-core neutronics/thermal-hydraulics (NE/TH) coupling analysis for Small Lead-based Fast Reactor (SLFR) was presented. The NE to TH coupling via the power distribution, whereas the TH to NE coupling via the material cross sections which related to the temperature distribution. In the NE module, a discrete ordinates (SN) nodal solver is implemented based on hexagonal prism mesh. In the TH module, a parallel channels model is implemented with each hexagonal fuel assembly a channel. The mass flow of each channel is searched according to the same pressure drop, the temperature and density of the coolant within each channel is calculated with one-dimensional axial heat convection model, the temperature distribution along the fuel pin is calculated with one-dimensional radial heat conduction model. In order to update the cross sections, a temperature dependent assembly homogenized microscopic cross section library is prepared in advance, based on the temperature distribution obtained from TH calculation, the cross section data required by the NE calculation is obtained by interpolation. The results of the NE/TH coupling analysis for SLFR indicate that the TH parameters (the maximum temperature of fuel, cladding, coolant and the maximum velocity of coolant) are all within the design limits, and the TH feedback provides a negative reactivity feedback (about -200 pcm) and has a fairly small effect on the power distribution (<0.5%).